KARAKTERISTIK IBU BERSALIN DI RSUD dr. R. GOETENG TARUNADIBRATAPURBALINGGA TAHUN 2011 – 2015 - Ikit Netra Wirakhmi (Viva Medika, 2016)
Childbirth is a physiological process of the uterus to remove the products of conception.Labor can walk normally, but if the delivery process encountered resistance should be performedsurgery. World Health Organization (WHO) states that globally, pregnancy and childbirth are the main cause of the persistently high Maternal Mortality Rate (MMR) and morbidity in women of reproductive age in countries - developing countries today. More than 300 million women in thecountry - poor and developing countries experienced a decline in health or sickness of the body,both in the short time until the condition is severe and long illness due to pregnancy and childbirthare experienced. Factors complications and maternal mortality and neonatal mostly occurred inthe period surrounding childbirth. Dr. R. Goeteng Tarunadibrata a government hospital type CPurbalingga which accommodates referral services from health centers and were heading type B(RS education). Medical and paramedical personnel in hospitals. dr. R. Goeteng Tarunadibratamust know the various characteristics of the women giving birth by maternal age so that they canmake early detection and prevention of complications of maternal and implementing safemotherhood in an effort to lower the maternal mortality ratio. To analyze the characteristics of women giving birth in hospitals dr. R. GoetengTarunadibrata Purbalingga years 2011 – 2015. The study was descriptive. The sampling technique in this research is consecutive sampling.The number of samples in this study is a random sampling with inclusion criteria, namely: (a)Mothers who deliver in hospitals dr. R. Goeteng Tarunadibrata Purbalingga at 1 January 2011 -December 31, 2015 and (b) RM complete patient data. Data taken from hospital medical recordsand analyzed using univariable (distribution, frequency and average). Medical Things that affect labor in dr. R. Goeteng Tarunadibrata Purbalingga Year 2011 -2015 consists of antepartum bleeding, prolonged labor, pre-eclampsia and eclampsia, serotinus,premature rupture of membranes, breech presentation, presentation latitude and parturitionprematurus. Characteristics of women giving birth in hospitals dr. R. Goeteng TarunadibrataPurbalingga years 2011 - 2015 is the largest and most categories premature rupture ofmembranes at the age of 20-35 years. Keywords: maternal characteristics, maternal age